Knowledge and practice of health workers about standard precaution: Special emphasis on medical waste management in Ethiopia - Alemayehu, Tadesse; Worku, Alemayehu; Assefa, Nega (International Journal of Infection Control, 2018)
Abstract Standard precautions are simple infection prevention and control measures that reduce the risk of transmission of bloodborne pathogens through exposure to blood and body fluids among patients and health workers. While compliance with standard precautions protects health workers from injury and related accidents, lack of compliance in basic standard precautions poses health workers to a significant health risks. This study has therefore assessed the knowledge and practices of standard precautions among health workers with special emphasis to healthcare waste management in the eastern part of Ethiopia. Institutional bases cross-sectional study was made on 818 healthcare workers under 65 health facilities. Data were collected using a self administered questionnaire. The collected data was analyzed using SPSS version 21 statistical software. Variables were analyzed with a univariate, bivariate and multivariable analysis methods. Factors associated with the outcome variable were identified by Generalized Estimating Equation. Out of the total respondents, 619(78.8%) responded that they ever heard about standard precautions. However, the overall knowledge about standard precaution was 54.6%. Variables such as recapping needles (AOR = 0.62, 95% CI = 0.22-0.85, P-value = 0.012), taking training about hygiene education (AOR = 1.77, 95% CI = 1.14-2.77, P-value = 0.014) and safe injection (AOR = 2.17, 95% CI = 1.54-3.06, P-value = 0.000). Knowledge of healthcare workers about universal precaution was low. Arranging in-service trainings could enhance the knowledge as well as the practice of health workers about safety precautions.